Analisis manajemen risiko kredit dan operasional pada perbankan syariah di era digital - Faizah, Nilna Alfa (Maliki Interdisciplinary Journal, 2026)
The advancement of digital technology has significantly transformed the banking industry, including Islamic banking. This transformation creates opportunities to improve efficiency and financial inclusion, but also introduces new risks, particularly credit and operational risks. This study aims to analyze the management of credit and operational risks in Islamic banking in the digital era and to identify appropriate mitigation strategies. The research uses a qualitative approach through literature review and descriptive analysis of industry reports, regulations, and risk management practices. The results show that digitalization increases credit risk complexity due to the use of alternative data and automated financing processes, which may lead to inaccurate credit assessments. Meanwhile, operational risk has also increased, especially related to cybersecurity threats, system failures, and technology-based fraud. To address these challenges, Islamic banks need to integrate digital-based risk management systems, strengthen internal controls, and improve human resource capabilities. In addition, the implementation of prudential principles and regulatory compliance plays a key role in maintaining operational stability. This study highlights the importance of adaptive and technology-based risk management frameworks for Islamic banking sustainability.